Covariation of dissolved nutrients and carbon in seawaters and sediment porewaters of western Svalbard fjords - Saghravani, Seyed Reza; Sen, Arunima; Hong, Wei-Li; Silberberger, Marc J. (Polish Polar Research, 2026)
We analyzed dissolved inorganic and organic carbon as well as dissolved inorganic nutrient concentrations in surface waters, bottom waters, water above sediments (i.e., core-top water), and sediment porewaters at 19 sites in western Svalbard fjords. Multiple Factor Analysis was used to identify common patterns in the water column and sediment layers. The analysis revealed a clear separation between surface waters and all deep water and porewater layers due to the strong summer stratification. Bottom waters, water above sediments, and both upper and lower porewater layers showed strong covariation across sites, with some sites consistently exhibiting low concentrations of carbon and nutrients, and others high concentrations across these layers. In contrast, surface water concentrations varied more independently from the other layers. Most of the variation among deep water and porewater layers was driven by a small number of sites that showed enrichment in dissolved inorganic carbon, dissolved organic carbon, and multiple nutrients in bottom waters and porewaters. Differences among sites in fjords often exceeded those between fjord systems, suggesting that deep water and porewater biogeochemical variability is structured more strongly by local basin conditions than by fjord-wide gradients. The strong covariation between bottom water and porewater chemistry suggests that bottom water concentrations integrate sedimentary signals at sites. This fine-scale, basin-level heterogeneity implies that fjord-averaged descriptions overlook biogeochemically distinct basins and that resolving individual basins and secondary fjords is necessary to anticipate how these systems respond to ongoing Arctic change. The patterns are likely shaped by local hydrographic conditions, including winter water formation, Atlantic Water intrusion, and freshwater inputs, all of which are changing rapidly in Arctic fjords. These changes may alter the persistence of local enrichment patterns and complicate predictions of future nutrient and carbon dynamics.